Rapid crystallization of all-inorganic CsPbBr3 perovskite for high-brightness light-emitting diodes - Ng, Yan Fong (2020)
Research into perovskite-based light-emitting diodes (PeLEDs) has been rapidly gaining momentum since the initial reports of green-emitting methylammonium lead bromide (CH3NH3PbBr3)-based devices were published. However, issues pertaining to its stability and morphological control still hamper progress toward high performing devices. Solvent engineering, a technique typically employed to modulate film crystallization, offers little opportunity for scale-up due to the tendency for inhomogeneous film growth and low degree of reproducibility. Here, we propose and show a simple gas-facilitated process to deposit a stable, all-inorganic perovskite CsPbBr3 film. The formation of smaller and less percolated grains, which gives rise to enhanced optical properties, highlights the importance of spatial charge confinement in the film. Consequently, the performance of our PeLEDs shows great improvement, with luminance as high as 8218 cd m–2 and turn-on voltage as low as 2.4 V. Concomitantly, the current efficiency and EQE of our device were increased to 0.72 cd A–1 and 0.088%, respectively. High reproducibility in the performance of PeLEDs fabricated using this process opens the path for large-area devices.